"Basis of yield component compensation in crop plants with special reference to field bean, Phaseolus vulgaris" by M. Wayne Adams, Crop Science (1967) 7, 505–510. Issue 2 (9th December 2020) - Sinclair, Thomas R.
Abstract: This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by M. Wayne Adams published in 1967 that provided original insights about compensation in the components of seed number and seed yield in determining crop yield. Adams reviewed experimental results in a large number of crop species and discovered a consistent negative correlation between seed number and mean seed mass. He labeled this negative correlation as "component compensation" in the formation of yield. He hypothesized that component compensation resulted from limiting nutrient‐metabolite availability to support developing reproductive structures. Ultimately, the retained seeds would be filled to the extent allowed by the supply of nutrient‐metabolites so that there was compensation between seed number and individual seed mass. Core Ideas: M. Wayne Adams in 1967 presented concepts about component compensation in yield formation. Adams reported a consistent negative correlation between seed number and mean seed mass. Component compensation resulted from limiting nutrient‐metabolite availability in seed growth.